Sosialisasi DAGUSIBU Untuk Meningkatkan Rasionalitas Penggunaan Obat Bagi Masyarakat Kerandangan Desa Senggigi - Wahida Hajrin; Windah Anugrah Subaidah; Yohanes Juliantoni (Universitas Mataram, 2020)
Senggigi village community has limitations in obtaining information about health, one of which is DAGUSIBU. DAGUSIBU is a way to get, use, store and dispose of medicines properly. The aim of this socialization was to inform about DAGUSIBU to the community so that medicines can be used rationally. The method used in the socialization is the delivery of material and direct examples related to the use of medicines that require special methods. The participants were very enthusiastic to attend the socialization, as evidenced by the many questions related to DAGUSIBU raised. This socialization increased participant’s knowledge about DAGUSIBU, they understand how to get, use, store and dispose of medicines in the right way.